Women in Iranian Puppet Theater: Interview with puppeteers of three generations (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
Interviews with Marzieh Baroumamand, Zahra Sabri e Fahime Mirzahosein, three prominent Iranian puppeteers from three generations who, notoriously, defined the directions of Puppetry in that country, addressing the role of women, contemporarily, in a traditionally masculine art, in the historical, social and political context of that country.
Keywords: women in puppet theater; sobrevento group; iranian puppet theater